2021
DOI: 10.21203/rs.3.rs-139876/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Evaluation of Readability of Information on the Internet Regarding Total Ankle Replacement

Abstract: Background:Health literacy is defined as the ability to understand basic health information with such competence as to be able to use this information to enhance health. Lower health literacy is associated with increased post-operative complications, reduced satisfaction and compliance. To ensure accessibility and comprehension by the general public, many international health organisations suggest that health literature has a reading grade level equivalent to the American sixth grade. However, previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…Instead, these patients and their families will peruse the internet as a 'quasi-second opinion' in an attempt 1 2 to gain more understanding of their injury and treatment [5]. Considering that internet penetrance is due to reach approximately 97% by 2023, and that research shows that 90% of patients believe the internet to be a reliable source of health care education and information, it can therefore be concluded that it is of the utmost important for the information on the internet to be as inclusive and accessible if we are, as physicians and health advocates, to ensure adequate health literacy [3][4][5][6][7]. Previous research in this area has shown that this is often not the case, orthopaedic related information in particular presented on the internet has been shown to vary widely in terms of accuracy, quality and readability levels.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, these patients and their families will peruse the internet as a 'quasi-second opinion' in an attempt 1 2 to gain more understanding of their injury and treatment [5]. Considering that internet penetrance is due to reach approximately 97% by 2023, and that research shows that 90% of patients believe the internet to be a reliable source of health care education and information, it can therefore be concluded that it is of the utmost important for the information on the internet to be as inclusive and accessible if we are, as physicians and health advocates, to ensure adequate health literacy [3][4][5][6][7]. Previous research in this area has shown that this is often not the case, orthopaedic related information in particular presented on the internet has been shown to vary widely in terms of accuracy, quality and readability levels.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy is defined as the comprehension of basic health information to a level of competence that allows the patient to use the information provided to make decisions that improve their health [8]. Previous studies in this field have comprehensively shown that lower levels of health literacy are keenly associated with increased post-operative complications and reduced rehabilitation compliance [6,7,[9][10][11][12]. Patients with poorer health literacy are also more likely to re-present to the hospital, have increased inpatient stay lengths, increased postoperative morbidity and mortality and lower post operative satisfaction [6,7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations